Polyphonic Theory in the Perspective of Intersexuality—The Relationship Between Bakhtin’s Polyphonic Novel and Polyphonic (Asian Journal of Social Science Studies, 2022)
The “polyphonic novel”, as defined by Mikhail Bakhtin, has a limited connection, commonality and a great difference with the “polyphonic music” in the history of Western music. The “interartistry (a concept derived from intersexuality, meaning intersexuality between two categories of art)” between the two can be examined in two ways: the intertextuality of the two theories themselves, and the profound artistic dialogue between Bakhtin and the composer Mikhail Glinka on an intellectual level that is not separated from the “intersubjectivity”. The heterogeneity between the two is mainly manifested in the dichotomous characteristics of “opposition and imitation” and “contradiction and harmony”. The “interartistry” of polyphonic novel and polyphonic music is examined from the perspective of “intersextuality”, which helps to fully understand the connection and difference between them and reduce the interdisciplinary misuse and abuse of related terms.